A Survey of Venous Thromboembolism (VTE) Prophylaxis in Obstetrics Patients in Iran - Majid Mokhtari; Khadijeh Nasri; Fatemeh Tara; Elahe Zarean; Sedigheh Hantoushzadeh; Mehrnaz Radmehr; Maryam Kashanian (Tehran University of Medical Sciences, 2019)
Objective: The purpose of the present study was a survey of venous thromboembolism (VTE) prophylaxis in obstetrics patients in Iran. Materials and methods: A national, multicenter, non-interventional, prospective study was performed on 1000 women at 11 different parts of Iran. Primary outcome was to assess the situation of VTE prophylaxis in pregnant and postpartum women and the secondary outcome was risk stratification in obstetrics patients and to evaluate the guideline adherence in physician's practice of VTE prophylaxis. Results: 1,036 women entered the final analysis. The three main VTE risk factors before hospitalization were BMI > 30 kg/m2, history of oral contraceptive (OCP) use, and the age over 35.VTE risk factors upon enrollment were detected in 780 (75.28%) patients. 219 women (28.07%) were deemed eligible for drug prophylaxis, however, only 37 women (17%) received it. A total of 113 (10.9%) patients received VTE prophylaxis, of which 76 (67.25%) women had no clear indications. Concordance between theory and practice was detected with a Cohen's Kappa coefficient to be 0.74 (p < 0.001), which fell within "good agreement". Multivariate analysis for association between VTE prophylaxis and VTE risk factors showed that history of VTE [OR = 9.06 (CI 95% 1.16 - 70.8) p = 0.036] was the most frequent risk factor for receiving VTE prophylaxis followed by obesity (BMI > 30 Kg/m2); [OR = 3.74 (CI 95% 1.79 - 5.69), p = <0.001], multiple pregnancy [OR= 2.81 (CI 95% 1.70 - 4.64), p = < 0.001] and age > 35 years; [OR =1.09 (CI 95% 0.82 - 1.21), p = 0.026]. Varicose Veins [OR= 0.22 (CI 95% 0.56 - 0.87), p = 0.031], PROM / PPROM [OR= 0.33 (CI 95% 0.12 - 0.91), p = 0.032] and history of using OCP [OR= 0.36 (CI 95% 0.24 - 0.53), p = < 0.001] were the most missed risk factors for receiving VTE prophylaxis respectively. Conclusion: History of VTE, obesity, multiple pregnancy and age > 35 years were the most frequent risk factors for receiving VTE prophylaxis and varicose veins, PROM / PPROM and history of using OCP were the most missed risk factors for receiving VTE prophylaxis.